Growth Test of Varieties of Palm Oil (Elaeis guineensis Jacq.) Seedlings with Hydroponic in Pre Nursery - Arung Buana; Rosmayati Rosmayati; Khairunnisa Lubis (Jurnal Agroekoteknologi, 2019)
The aim of this research was to test the growth of palm oil varieties seedlings with some concentration of nutrients. This research was conducted at Greenhouse Faculty of Agriculture University of Sumatera Utara, from August to October 2017. The research design used  randomized block design (RBD) with 2 factors. The first factor was varieties consist of 3 varieties namely DxP Avros, DxP Langkat, and DxP Yangambi. The second factor is the concentration consisting of 4 levels  (8 HS, 1 HS, 1,2 HS and 1,4 HS). The observed variables were plant height (6, 8, 10, and 12 weeks after planting), number of leaves, stem diameter, root number and root length. The results showed that varieties significantly different to the plant height, stem diameter, and root length. The different concentration of nutrients had no significantly effect to all observed variables, and there was no interaction between the two treatments. 6 observed variables had high heritability at plant height 6, 10, and 12 weeks after planting, number of leaves 8 weeks after planting, stem diameter, and root length characters.